2009
DOI: 10.7748/ns2009.05.23.35.41.c6958
|View full text |Cite
|
Sign up to set email alerts
|

Advanced physical assessment: the role of the district nurse

Abstract: This article describes an initiative by an NHS trust to support its district nurses in developing and using physical examination skills as part of patient assessment. The article outlines the process and suggests that the initiative is important to help meet the needs of older patients with long-term conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Many nurses at community hospitals deal with various diseases, and in their workplaces, an effective physical assessment may be useful in improving patients' conditions. 5 To establish an educational system for effective physical assessment, it is essential to provide a clear picture of the present state of the education provided on performing physical assessments to nurses at community hospitals.…”
mentioning
confidence: 99%
“…Many nurses at community hospitals deal with various diseases, and in their workplaces, an effective physical assessment may be useful in improving patients' conditions. 5 To establish an educational system for effective physical assessment, it is essential to provide a clear picture of the present state of the education provided on performing physical assessments to nurses at community hospitals.…”
mentioning
confidence: 99%
“…The participants reported that the medical checkups include physical examination, body weight measurement, tension check, eyes examination, Mid-Upper Arm Circumference, abdominal examination, fetal heartbeat examination, and ankle and foot examination for swelling. Baid, Bartlett, Gilhooly, Illingworth, and Winder (2009) reported that holistic nursing care requires patient assessment based on information obtained from interviews, physical examinations, and assessments of patient history. In addition, nurses must examine their client's head, hair, eyes, nose, ears, teeth, mouth, neck, breasts, respiratory system, cardiac system, and abdomen (measuring symphysis-fundus height, leopold, fetal pulse rate, and hyperpigmentation), extremity reflexes, pelvis, and rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Physical assessment is a framed consultation and physical examination by a practitioner, to gather data for a medical diagnosis, which informs decisions about a patient's treatment (Baid 2009). Medical physical assessment education and training were introduced to registered nurses' (RNs) roles in the UK in 1990s.…”
Section: Definition Of Physical Assessmentnurses and Doctorsmentioning
confidence: 99%
“…Despite lack of evidence about the efficacy of PAS, and its purpose for nursing work, PAS was introduced to RNs' scope of practice in the UK in the late 1990s. RNs were trained to undertake PAS based on a medical examination framework to appraise patients' signs and symptoms (West 2006, Rushforth et al 2006 and where possible make diagnoses in the absence of a medical doctor (Baid 2009).…”
Section: Definition Of Physical Assessmentnurses and Doctorsmentioning
confidence: 99%